Ocular mainifestations in multitransfused thalassemic children on chelation therapy - J., Sowmya; Rudrappa, Sudha; G., Girish; H. N., Yashwanth Raju (International Journal of Contemporary Pediatrics, 2018)
Background: Beta-thalassemia is the most common form of thalassemias. It is due to mutations involving the beta globin gene. The objective of this study was to study ocular manifestations in multi transfused thalassemic children and to assess the possible ocular side-effects with deferasirox. Methods: This was a prospective correlational study. After obtaining institutional ethical committee clearance, children with beta-thalassemia who came for regular blood transfusions were assigned into group A and group B based on whether they received deferasirox therapy or not. They were sent for detailed ophthalmological examination. The details about number of blood transfusions, serum ferritin and chelation therapy was obtained from the treatment records. The ocular manifestations were documented and later correlated to the blood transfusions, Serum ferritin levels and the chelation therapy. Results: Out of 50 children, 42 children belonged to group A and 8 belonged to group B. The male to female ratio was 2.2:1 in group A and 1:3 in group B respectively. The number of blood transfusions received was 67.7 versus 21.87 in group A and B respectively. The mean frequency of blood transfusions was 5.26 weeks vs 3.8 weeks in group A and group B respectively. Mean serum ferritin was higher in group A (912.19 mcg/l) compared to 665 mcg/l in group B. Out of 50 children7 had ocular findings (p value: 0.176), statistically not significant. All of them belonged to group A. Only 3 of them had lenticular opacities and 4 of them had refractory errors. The mean serum ferritin and the number of blood transfusions received were higher in children with ocular findings than in those with no ocular manifestations. Serum ferritin in those with lenticular opacities was 1363.66 mcg/l and in those with refractory error was 987.25mcg/l. The average blood transfusion received was 104.6 in those with lenticular opacities and 62.25 in those with refractory errors. Conclusions: Regular ocular examinations can aid in preventing, delaying or reducing the ocular complications in transfusion dependent beta-thalassemia major children.